Administrative Burden of Semarang Regency Spatial Planning Office Indonesia - Muhammad Rizqi Havizt Saputra; Nursukma, Dzulfiqar Prakoso (HM Publisher, 2024)
This article comprehensively examines the administrative burden on Semarang Regency's Spatial Planning Office and the ways in which it can be addressed. From a HAN perspective, administrative burden is often seen as a consequence of the regulation and administration necessary to ensure that the government operates in accordance with the law and is transparent and accountable. The method chosen in this research is a descriptive qualitative research method with a socio-legal approach. The subjects in this research are community stakeholders of Semarang Regency, the Head of Semarang Regency Spatial Planning Office, as well as civil apparatus. This research found that strategic steps can be taken to reduce it significantly. It should be recognized that administration is an integral part of every organization's operation, and some level of regulation and governance is necessary to ensure transparency, accountability, and policy compliance. In that regard, agencies can reduce the administrative burden by implementing advanced information technology, automation of routine processes, and bureaucratic reforms to improve efficiency. Human resource training and development can also play a role in improving employees' skills in managing administrative tasks. In addition, stakeholder engagement and inter-agency cooperation can help simplify regulations and reduce administrative overlap. This research recommends this approach, which can help create a more efficient administrative environment that is responsive to changing organizational dynamics and the external environment.